Genetic and Diet-Induced Obesity Increased Intestinal Tumorigenesis in the Double Mutant Mouse Model Multiple Intestinal Neoplasia X Obese via Disturbed Glucose Regulation and Inflammation - Ha Thi Ngo (Journal of Obesity, 2015)
We have studied how spontaneous or carcinogen-induced intestinal tumorigenesis was affected by genetic or diet-induced obesity in C57BL/6J-ApcMin/+ X C57BL/6J-Lepob/+ mice. Obesity was induced by the obese (ob) mutation in the lep gene coding for the hormone leptin, or by a 45% fat diet. The effects of obesity were examined on spontaneous intestinal tumors caused by the multiple intestinal neoplasia (Min) mutation in the adenomatous polyposis coli (Apc) gene and on tumors induced by the dietary carcinogen 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP). F1 ob/ob (homozygous mutated) mice had increased body weight (bw) and number of spontaneous and PhIP-induced small intestinal tumors (in ApcMin/+ mice), versus ob/wt (heterozygous mutated) and wt/wt mice (homozygous wild-type). A 45% fat diet exacerbated bw and spontaneous tumor numbers versus 10% fat, but not PhIP-induced tumors. Except for bw, ob/wt and wt/wt were not significantly different. The obesity caused hyperglucosemia and insulinemia in ob/ob mice. A 45% fat diet further increased glucose, but not insulin. Inflammation was seen as increased TNFα levels in ob/ob mice. Thus the results implicate disturbed glucose regulation and inflammation as mechanisms involved in the association between obesity and intestinal tumorigenesis. Ob/ob mice had shorter lifespan than ob/wt and wt/wt mice.